2019
DOI: 10.1016/j.heliyon.2019.e02106
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sediment yield at Kaduna watershed, Nigeria using soil and water assessment tool (SWAT) model

Abstract: Over the years, sedimentation has posed a great danger to the storage capacity of hydropower reservoirs. Good understanding of the transport system and hydrological processes in the dam is very crucial to its sustainability. Under optimal functionality, the Shiroro dam in Northern Nigeria can generate ∼600 MW, which is ideally sufficient to power about 404,000 household. Unfortunately, there have not been reliable monitoring measures to assess yield in the upstream, where sediments are sourced into the dam. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…5. This could results from observational data error, human interaction such as mining and quarry on the watershed (Daramola et al 2019). There are many quarries and concreate stations observed in the upper part of the watershed.…”
Section: 2sediment Yield Outputsmentioning
confidence: 99%
See 1 more Smart Citation
“…5. This could results from observational data error, human interaction such as mining and quarry on the watershed (Daramola et al 2019). There are many quarries and concreate stations observed in the upper part of the watershed.…”
Section: 2sediment Yield Outputsmentioning
confidence: 99%
“…The Soil and Water Assessment Tool (SWAT) developed by Arnold et al (1998) is a physical based hydrological model that are used widely in literature for different purposes. Several researchers have been studied with SWAT for simulating runoff (Alipour and Hosseini 2018;Ang and Oeurng 2018;Jakada and Chen 2020), sediment yield (Xu et al 2009;Rodríguez-Blanco et al 2016), and water quality (Qi et al 2020;Abbaspour et al 2007); determine soil erosion areas (Vigiak et al 2015;Dutta and Sen 2017;Daramola et al 2019), in different watersheds. Additionally, the model has been applied to the impact of climate change (Zhang et al 2014); land use, and land cover changes; (Abellan et al 2019;Worku et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A sensitivity analysis for the simulated stream flow and sediment was carried out to determine the most sensitive parameter with the greatest impact on model results. According to the SWAT manual and the literature (Khelifa et al, 2017, Yuan & Forshay, 2019, Daramola et al, 2019, nine (Table 2) and seven (Table 3) parameters for stream flow and sediment were respectively selected as the initial input for the model sensitivity analysis.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Abam (2001) confirmed that river Kaduna, a tributary of the Shiroro river (the study area) receives sediment influx of about 96 t/km 2 (66.6x10 6 ) ton per year. While Daramola (2019) affirmed that Shiroro dam received annual sediment influx of about 84.1 t/ha/yr from the four reaches that supply water to the dam namely Kaduna, Gutalu, Sarkinpawa and Dinya. Adeogun, Sule and Salami (2018), corroborates this fact that information gathered on the three Nigeria hydropower reservoirs (Shiroro, Kanji and Jebba) confirmed that the storage capacities of these dams have been critically affected by substantial movement and deposition of sediment from upstream of the dams to the reservoirs.…”
Section: Introductionmentioning
confidence: 97%